NICKEL OXIDE(NiO) NANOTECHNOLOGY FOR ANTI-FUNGAL APPLICATIONS: A COMPREHENSIVE REVIEW OF CURRENT TRENDS AND FUTURE PROSPECTS - Alif Furqan; Diki Miswar; Abd. Mujahid Hamdan (Indonesian Journal of Environmental Sustainability, 2023)
Fungal infections are known to be a common global health problem, especially as resistance to conventional antifungal drugs increases. Innovative solutions are needed to overcome this problem. This review aims to explore the potential application of nanotechnology to nickel oxide materials in inhibiting the growth of pathogenic fungi, as well as investigating the ability of nanosized nickel oxide as an innovative option in overcoming antifungal problems. The use of nickel oxide nanomaterial as an antifungal agent can produce efficient healing in treating fungal infections which are currently difficult to treat. Information explaining the potential side effects or long-term effects of this method is essential to ensure that the use of this agent does not harm the patient's health. Nano-sized nickel oxide has the ability to interact with other living things in an ecosystem. Therefore, to understand possible environmental risks, research is needed on the concept of ecological impacts on these materials. To increase awareness of the potential use of nano nickel oxide in the treatment of fungal infections, it is important to make this nickel oxide material available to the general public. Global consistency of patient treatment can be ensured through the establishment of well-defined and standardized protocols for the application of nickel oxide nanoparticles in the treatment of fungal infections.